Biotinylated photoactive Pt() anticancer complexes - Shi, Huayun; Imberti, Cinzia; Huang, Huaiyi; Hands-Portman, Ian; Sadler, Peter J (Chemical communications (Cambridge, England), 2020)
Novel biotinylated diazido-Pt( iv ) complexes exhibit high visible light photocytotoxicity while being stable in the dark. Photocytotoxicity and cellular accumulation of all- trans -[Pt(py) 2 (N 3 ) 2 (biotin)(OH)] ( 2a ) were enhanced significantly when bound to avidin; irradiation induced dramatic cellular morphological changes in human ovarian cancer cells treated with 2a . Novel biotinylated diazido-Pt( iv ) complexes exhibit high visible light photocytotoxicity while being stable in the dark.